CTA-for-All: Impact of Emergency Computed Tomographic Angiography for All Patients With Stroke Presenting Within 24 Hours of Onset. Issue 1 (January 2020) - Mayer, Stephan A.; Viarasilpa, Tanuwong; Panyavachiraporn, Nicha; Brady, Megan; Scozzari, Dawn; Van Harn, Meredith; Miller, Daniel; Katramados, Angelos; Hefzy, Hebah; Malik, Shaneela; Marin, Horia; Kole, Maximilian; et al.
Abstract : Background and Purpose—: We sought to evaluate the impact of a Computed Tomographic Angiography (CTA) for All emergency stroke imaging protocol on outcome after large vessel occlusion (LVO). Methods—: On July 1, 2017, the Henry Ford Health System implemented the policy of performing CTA and noncontrast computed tomography together as an initial imaging study for all patients with acute ischemic stroke (AIS) presenting within 24 hours of last known well, regardless of baseline National Institutes of Health Stroke Scale score. Previously, CTA was reserved for patients presenting within 6 hours with a National Institutes of Health Stroke Scale score ≥6. We compared treatment processes and outcomes between patients with AIS admitted 1 year before (n=388) and after (n=515) protocol implementation. Results—: After protocol implementation, more AIS patients underwent CTA (91% versus 61%; P <0.001) and had CTA performed at the same time as the initial noncontrast computed tomography scan (78% versus 35%; P <0.001). Median time from emergency department arrival to CTA was also shorter (29 [interquartile range, 16–53] versus 43 [interquartile range, 29–112] minutes; P <0.001), more cases of LVO were detected (166 versus 96; 32% versus 25% of all AIS; P =0.014), and more mechanical thrombectomy procedures were performed (108 versus 68; 21% versus 18% of all AIS; P =0.196). Among LVO patients who presented within 6 hours of last known well, median time from last known well to mechanical thrombectomy was shorter (3.5 [interquartile range, 2.8–4.8] versus 4.1 [interquartile range, 3.3–5.6] hours; P =0.038), and more patients were discharged with a favorable outcome (Glasgow Outcome Scale 4–5, 53% versus 37%; P =0.029). The odds of having a favorable outcome after protocol implementation was not significant (odds ratio, 1.84 [95% CI, 0.98–3.45]; P =0.059) after controlling for age and baseline National Institutes of Health Stroke Scale score. Conclusions—: Performing CTA and noncontrast computed tomography together as an initial assessment for all AIS patients presenting within 24 hours of last known well improved LVO detection, increased the mechanical thrombectomy treatment population, hastened intervention, and was associated with a trend toward improved outcome among LVO patients presenting within 6 hours of symptom onset. Abstract : Supplemental Digital Content is available in the text.